2016
DOI: 10.1186/s12885-016-2360-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mTOR-inhibitors and mycophenolic acid on human cholangiocellular carcinoma and cancer associated fibroblasts

Abstract: BackgroundThe incidence of Cholangiocellular Carcinoma (CCA) is increasing in the western world. The tumour has a high proportion of desmoplastic stroma and is correlated with a worse prognosis when cancer associated myofibroblasts (CAFs) are present. Recent studies showed promising results after liver transplantation (LTx) in non-resectable early stage CCA. Mycophenolic acid (MPA) and the mTor inhibitor Everolimus are used to prevent organ rejection but recently were shown to exhibit an antiproliferative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 67 publications
0
26
0
2
Order By: Relevance
“…Numerous studies have demonstrated that the IGF1R/IRS1 pathway was involved in cell proliferation and metastasis control of several solid tumors . mTOR is associated with various biological processes including cell proliferation, differentiation, migration and invasion, angiogenesis, survival as well as tumorigenesis . Recent studies demonstrated that mTOR also plays an important role in chemotherapeutic resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the IGF1R/IRS1 pathway was involved in cell proliferation and metastasis control of several solid tumors . mTOR is associated with various biological processes including cell proliferation, differentiation, migration and invasion, angiogenesis, survival as well as tumorigenesis . Recent studies demonstrated that mTOR also plays an important role in chemotherapeutic resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that co-culture of CCA cells with either CAFs or HSCs resulted in increased cancer cell migration and/or invasiveness, in vitro 2831 . In addition, Claperon et al demonstrated that subcutaneous co-injection of CCA cells with liver myofibroblasts in immunodeficient mice enhanced both tumor growth and the incidence of intrahepatic micrometastases, compared with mice inoculated with cancer cells alone 32 .…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…Indeed, high stromal expression of α-SMA was reported as an independent prognostic factor for overall and disease-free survival[27,29]. In line with these findings, both incubation of CCA cells with CAF conditioned medium and co-culture of CCA cells with CAFs resulted in increased cancer cell proliferation and migration, in vitro [27,30]. On the contrary, slighter pro-tumorigenic effects were elicited by liver fibroblasts isolated from the peritumoral areas, arguing for a deep biological gap between CAFs and their naïve counterpart (see below)[27].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 83%
“…By translating these findings in an in vivo , orthotopic syngeneic rat model of CCA, navitoclax markedly reduced tumor growth and metastasis, and significantly improved survival, an effect related to a quantitative depletion of CAFs from the stroma. Taking a different approach, the mammalian target of rapamycin inhibitor everolimus, in addition to directly reduce CCA cell proliferation and invasion[100], was reported to hamper the cross-talk between CAFs and CCA cells, by both impairing the activation of CAF-induced motogenic pathways in cancer cells, and inhibiting the secretion of tumor-promoting cyto/chemokines by CAFs[30]. Interestingly, everolimus is already an FDA-approved drug for the treatment of breast, neuroendocrine and renal cell carcinomas[101].…”
Section: The Trs As Potential Therapeutic Targetmentioning
confidence: 99%